The Impact of Social Intelligence of Administrative Leaders on Improving Organizational Effectiveness - Hasan, Emran; Sulayman Al-Naas (International Journal of Economics (IJEC), 2025)
Background: The social intelligence of leaders has become a very popular project; however, research conducted by practitioners to date does not provide convincing evidence of the effectiveness of organizations through the development of social intelligence. This study aimed to identify the impact of the social intelligence of administrative leaders on improving the effectiveness of the General Electricity Company in Libya. Methodology: The study population consisted of employees of the General Electricity Company. We tested our hypothesis using field data from 387 employees working at the General Electricity Company, using a questionnaire consisting of seven items to measure the social intelligence of administrative leaders and seven items to measure the effectiveness of the organization (the General Electricity Company). A mixed methodology (quantitative and qualitative) was used, and the SPSS program was used to analyze the data collected through the questionnaire. Statistical results indicate that social intelligence has a significant impact on organizational effectiveness through the availability of several characteristics, such as social acumen, emotional skills, and flexibility in dealing with employees. The study also revealed that a socially intelligent leader must demonstrate a genuine interest in their team and empathize with their feelings. Thus, social intelligence enables leaders to positively influence and persuade others of their viewpoints without resorting to coercive authority. Furthermore, the results showed a direct correlation between leaders' social intelligence and enhanced organizational effectiveness, as it allows them to understand the emotions and motivations of organizational members, communicate effectively, contribute to building trusting relationships, and manage conflict. The study also found that leaders with high social intelligence significantly contributed to increased team motivation, enhanced employee collaboration, and the creation of a positive and productive work environment, which positively impacted productivity and service delivery.